2015
DOI: 10.1186/s12889-015-2350-9
|View full text |Cite
|
Sign up to set email alerts
|

A telephone survey of factors affecting willingness to participate in health research surveys

Abstract: BackgroundIn recent years, reduced participation has been encountered across all epidemiological study designs, both in terms of non-response as well as refusal. A low response rate may reduce the statistical power but, more importantly, results may not be generalizable to the wider community.MethodsIn a telephone survey of 1413 randomly selected members of the Australian general population and of 690 participants sourced from previous studies, we examined factors affecting people’s stated willingness to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
85
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 32 publications
13
85
3
Order By: Relevance
“…For example, while we had relatively equal distributions across educational categories, the sample was weighted toward females. This is not surprising given there is clear evidence women are more likely to participate in scientific studies than men (24)(25)(26). These factors could suggest our sample may not be entirely reflective of the greater Australian population.…”
Section: Discussionmentioning
confidence: 90%
“…For example, while we had relatively equal distributions across educational categories, the sample was weighted toward females. This is not surprising given there is clear evidence women are more likely to participate in scientific studies than men (24)(25)(26). These factors could suggest our sample may not be entirely reflective of the greater Australian population.…”
Section: Discussionmentioning
confidence: 90%
“…This is not surprising, given that women are more often willing to participate in and successfully complete telephone surveys (Glass et al, 2015). The effect of overrepresentation of females in the study is unclear.…”
Section: Limitationsmentioning
confidence: 99%
“…While our study confirmed that consulting patients and families about this sensitive topic is feasible in Australia, this consultation did not happen at a time of acute medical crisis. It could be argued that our study did not take into account patient and family preferences at those critical times, as studies have shown that preferences can change over time depending on a person's state of health . However, we believe the views our participants are further enriched by the ability for retrospection without the influence of an acute emotion.…”
Section: Discussionmentioning
confidence: 95%